Subjective well-being in Portuguese children and adolescents: Differences according to their age, gender and ethnicity - Alexandre, J.; Joana Baião; Carvalho, H.; Monteiro, L.; Ana Mota; Mafalda Visitação (17th European Conference on Developmental Psychology, 2015)
The Children’s Worlds Study attend to provide insights on children’s subjective well-being. The present paper aims to show how variables like ethnicity, sex or age influence subjective well-being in a sample of Portuguese children and adolescents from the Lisbon urban area. Preliminary data (N = 331 participants) showed that subjective well-being vary according to such socio-demographic variables: black children showed less satisfaction in material well-being , family well-being , interpersonal well-being and with their neighborhood. Black girls showed less satisfaction at an interpersonal level and with their neighborhoods. Results will be discussed in the light of the theoretical approaches on subjective well-being and children’s subjective well-being in particular.